2010
DOI: 10.1186/1471-2407-10-446
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Cantonese diet and nasopharyngeal carcinoma risk: a large-scale case-control study in Guangdong, China

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is rare in most parts of the world but is a common malignancy in southern China, especially in Guangdong. Dietary habit is regarded as an important modifier of NPC risk in several endemic areas and may partially explain the geographic distribution of NPC incidence. In China, rapid economic development during the past few decades has changed the predominant lifestyle and dietary habits of the Chinese considerably, requiring a reassessment of diet and its potential influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 27 publications
6
110
3
6
Order By: Relevance
“…The prevalence of NPC is skewed geographically with South-East Asia, the middle East, and Northern Africa being disproportionately affected (3). Epidemiologic factors associated with NPC include tobacco (4) and alcohol use (5), consumption of salt-preserved foods (6,7), and smoke inhalation from cooking fires (8,9). A pathologic classification of the disease into keratinizing squamous cell carcinoma, nonkeratinizing (differentiated and undifferentiated), and basaloid squamous cell carcinoma has been proposed (10).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NPC is skewed geographically with South-East Asia, the middle East, and Northern Africa being disproportionately affected (3). Epidemiologic factors associated with NPC include tobacco (4) and alcohol use (5), consumption of salt-preserved foods (6,7), and smoke inhalation from cooking fires (8,9). A pathologic classification of the disease into keratinizing squamous cell carcinoma, nonkeratinizing (differentiated and undifferentiated), and basaloid squamous cell carcinoma has been proposed (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been proved to enhance the risk of NPC, including Epstein-Barr virus (EBV), smoking, alcohol consumption, salt-preserved foods and family history of cancer, etc (Chien et al, 2001;Jia et al, 2010;Ji et al, 2011;Hashim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been proved to enhance the risk of NPC, including Epstein-Barr virus (EBV), smoking, alcohol consumption, salt-preserved foods and family history of cancer, etc (Chien et al, 2001;Jia et al, 2010;Ji et al, 2011;Hashim et al, 2012).Extensive investigations have showed that the ABO blood group might be associated with risk to certain malignancies (Iodice et al, 2010;Gates et al, 2011;Joh et al, 2012;Wang et al, 2012;Zhang et al, 2014). A previous study suggested that blood type A or AB was associated with an increased risk of NPC and male patients with blood group A had higher rates of distant …”
mentioning
confidence: 99%
“…EpsteinBarr virus infection, tobacco smoking, alcohol consumption, and occupational exposure to wood dust, as well as high salt consumption, play an important role in NPC development (Hildesheim et al, 2001;Jia et al, 2010;Polesel et al, 2011;Fachiroh et al, 2012;Song and Yang, 2013). Because 80% of NPC cases are diagnosed late because of the deep location of the suspected tumor and non-specificity of initial symptoms, the survival of nasopharyngeal carcinoma is poor (Xi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%